2016
DOI: 10.1097/shk.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Systemic Hypertension and Left Ventricular Hypertrophy on Outcome of Cardiopulmonary Resuscitation and Therapeutic Hypothermia in a Cardiac Arrest Model of Rat

Abstract: In this rat model, systemic hypertension and LVH did not affect ROSC. However, survival was dismal due to elevated severity of cardiac and cerebral injury in hypertensive animals regardless of short-duration hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Ischemic heart disease and diabetes were present in around 30% and 10% in the TTM-trial and the HACA study. The few studies that evaluated animals with comorbidities did not consistently favour TTM [69][70][71][72]. Outcome was evaluated at 6 months in both the TTM-trial and the HACA study, a time point rare in animal studies; only 14 of 481 histological comparisons were made at 6 months or later and no comparisons of neurobehaviour and mortality were made at this time.…”
Section: Stair Analysismentioning
confidence: 99%
“…Ischemic heart disease and diabetes were present in around 30% and 10% in the TTM-trial and the HACA study. The few studies that evaluated animals with comorbidities did not consistently favour TTM [69][70][71][72]. Outcome was evaluated at 6 months in both the TTM-trial and the HACA study, a time point rare in animal studies; only 14 of 481 histological comparisons were made at 6 months or later and no comparisons of neurobehaviour and mortality were made at this time.…”
Section: Stair Analysismentioning
confidence: 99%
“…The diabetes mellitus induced in the present study triggered cardiac hypertrophy irrespective of dietary fortifications. Diabetes in general, and especially type II diabetes, causes hypertension in humans, and this has also been proven in rats [56,57]. Hypertension in turn leads to cardiac hypertrophy [58,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Rats aged 2–3 months can generally reach 250–450 g. What we tend to overlook here is that the majority of CA patients are not healthy, they are usually complicated with organic disease. A study of hypertensive CA rats showed that hypertension groups got more severe brain damage and lower survival than the control group ( Wang et al, 2016 ). It reflected differences between healthy CA patients and CA patients with other co-morbidities.…”
Section: Attributes Of Rats For Modeling Acamentioning
confidence: 99%